Digital tools for soil stewardship: how Internet access drives farmland conservation in rural China? - Zhai, Xizi; Zheng, Yangyang; Gao, Xinrui (Frontiers in Sustainable Food Systems, 2025)
With the popularization of Internet technology in rural areas, its impact on sustainable agricultural development has become a hot research topic. Based on 1,728 farm household data from 14 provinces (districts), this paper employed the propensity score matching method and instrumental variable method to test and analyze the impact of Internet use on farm households’ farmland quality protection behavior. The study found that the use of the Internet significantly promoted the farmer’s cultivated land quality protection behavior. Compared to the non-Internet farmer, the use of the Internet enabled farmers to adopt an average of 0.318 more farmland quality protection technologies. Heterogeneity analysis shows that the use of the Internet is significantly positive among low-education farmers and villages with water security, and the role of the Internet is greater for trained farmers, small-scale farmers, high-income farmers, poor village farmers, and farmers in Western China. In addition, Internet use has a significant contribution to arable land quality protection measures such as straw return, deep ploughing and loosening, soil testing of fertilizers and planting of green manure crops. Therefore, the construction of rural Internet should be strengthened, and the heterogeneity of farmers and villages should be considered in policy formulation.